Quantum image encryption algorithm based on four-dimensional chaos - Liu, Xiao-Dong; Chen, Qian-Hua; Zhao, Run-Sheng; Liu, Guang-Zhe; Guan, Shuai; Wu, Liang-Long; Fan, Xing-Kui (Frontiers in Physics, 2024)
In order to optimize the quantum decryption image quality and computational complexity, we propose a quantum image encryption algorithm based on four-dimensional chaos. The image is represented using the GQIR quantum encoding method, and the key generated based on the four-dimensional chaotic system is added to the entire quantum image representation and processing process. We simulated this process in the Python environment, and the information entropy analysis experiment showed that the information entropy of the three encrypted images reached above 7.999, so the system has good encryption. At the same time, the correlation of the pixel distribution after the encryption algorithm is weak, which proves that the control parameters of the chaotic system can effectively reduce the correlation between pixels in the image. In the final key space analysis, the key space issued by our encryption can reach 10 140 ≫ 2 128 . Therefore our method is resistant to destructive attacks and can produce scrambled images with higher encryption and usability